Efecto del decocto de las hojas de plantago major l. sobre la inflamación intestinal inducida en rattus rattus var albinus - Medina Onsihuay, Roberto Carlos (2011)
Owing to the frequent popular use of vegetal species Plantago major L, commonly known as "Llantén" in the treatment of digestive alterations and other inflammations, we sought to investigate the effect of decoct of the leaves of Plantago major L. in intestinal inflammation induced in Rattus rattus albinus var. For this purpose we designed a experimental study in vivo considered 6 groups: White Group, Control, Standard and Problem I, II and III. Intestinal inflammation was induced using the experimental model proposed by Yamada et al modified, for this purpose we used 36 Rattus rattus var albinus. The decocts of the leaves of Plantago major L. were prepared at 5% (37.09 mg/kg), 7.5% (54.80 mg/kg) and 10% (75.16 mg/kg), and were administered twice daily respectively; then was realized complete removal of the intestine of all specimens and the respective histopathologic study, considering the macroscopic and microscopic analysis. The results were statistically analyzed by SPSS statistical support, finding that decocts had anti-inflammatory effect and tissue regeneration, standardizing the architecture of the mucosa and attenuated leukocyte infiltration.